English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-03-09 01:57:31 · 14 answers · asked by Anonymous in Science & Mathematics Mathematics

14 answers

First, multiply it through.

You'll end up with:
8 - 4i + 20i - 10i^2 =
8 - 10i^2 + 16i

Since you know that i^2 = -1, you plug that in to get:
8 + 10 + 16i =
18 + 16i

Then, you simply factor out 2 to make this as simple as possible:

2(9 + 8i)

2007-03-09 02:00:36 · answer #1 · answered by Rev Kev 5 · 0 1

(2+5i)(4-2i)=
2(4 - 2i) + 5i(4 - 2i) =
8 - 4i + 20i - 10i² =
10 + 16i + 8 = 16i +18
:=:

2007-03-09 11:09:56 · answer #2 · answered by aeiou 7 · 1 0

(2+5i) (4 -2i) = 8 + 16i -10i²

ax² + bx + c = 0

-10i² +16i + 8 = 0 ...................ans


Using Quadratic equation:

i = [-b + √b²-4ac]/2a

i =[-16 + √16²-4(-10) (8)]/2(-10)

=[-16- √(256 +320)]/-20

=[-16-(√576)]/-20

=[-16-24]/ -20

= - 40/-20

i = 2 ................ans for finding the value of i

To check this, we have;

(2+5i) (4 -2i) = -10²i + 16i+ 8

8 + 16i -10i² = -10²(2) +16(2) + 8

8 + 16(2) -10(2)² = -100(2²) +32 +8

8+ 32-100(4)= -100(4) +32 +8

- 360 = - 360

2007-03-09 10:35:48 · answer #3 · answered by edison c d 4 · 0 1

(2 + 5i)(4 - 2i) = (2 + 5i)*4 - (2 + 5i)*2i = 8 + 20i - 4i + 10 =
= 18 + 16i

2007-03-09 10:02:43 · answer #4 · answered by Amit Y 5 · 0 1

distribute first the numerical values for you to simplify it easily..

(2 + 5i)(4 - 2i)= 8 - 4i + 20i - 10i2

= 8+16i-10i2 i2= -1
=18+16i

2007-03-09 10:07:28 · answer #5 · answered by aira mesoj 1 · 0 0

(2 + 5i)(4 - 2i) =

8 + 20i - 4i - 10i²

8 + 16i - 10i²

8 + 16i - 10(- 1)

8 + 16i + 10

16i + 18

- - - - - - - - -s-

2007-03-09 10:10:36 · answer #6 · answered by SAMUEL D 7 · 0 0

(2 + 5i)(4 - 2i)
= 2(4 - 2i) + 5i(4 - 2i)
= 8 - 4i + 20i - 10i^2
= 8 + 16i + 10 .......................i^2 = -1
= 18 + 16i

2007-03-09 10:02:54 · answer #7 · answered by ganesan 2 · 1 0

Remember that i = sqrt(-1), so i^2 = -1.


(2 + 5i)(4 - 2i)

FOIL it out.

8 - 4i + 20i - 10i^2

8 + 16i - 10i^2

But i^2 = (-1),

8 + 16i - 10(-1)

8 + 16i + 10

18 + 16i

2007-03-09 10:01:52 · answer #8 · answered by Puggy 7 · 2 0

î = √(-1)
î² = -1

(2+5i)(4-2i)=
8 - 4î + 20î - 10î² =
8 - 16î - 10î² =
8 - 16î - 10(-1) =
8 - 16î + 10 =
18 + 16î

2007-03-09 10:16:02 · answer #9 · answered by Brenmore 5 · 1 0

remember foil
front outer inner last
6+-4i+20i+-10i^2
-10i^2 +16i+6

Is i a variable or the imaginary number (for sqrt -1)?

2007-03-09 10:08:08 · answer #10 · answered by Matthew P 4 · 0 0

fedest.com, questions and answers